2016
DOI: 10.1163/15691624-12341303
|View full text |Cite
|
Sign up to set email alerts
|

From Body Image to Emotional Bodily Experience in Eating Disorders

Abstract: This paper is a critical analysis and overview of body image conceptualization and its scope and limits within the field of eating disorders (eds) up to the present day. In addition, a concept ofemotional bodily experienceis advanced in an attempt to shift towards a more comprehensive and multidimensional perspective for thelived bodyof these patients. It mainly considers contributions from phenomenology, embodiment theories and a review of the empirical findings that shed light on the emotional bodily experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 42 publications
2
30
0
2
Order By: Relevance
“…Health services focusing, for example, on lifestyle-changing programs might increase attempts to control the obese body, but this can also lead to an increased objectification of the body (Grønning et al, 2013). Gaete and Fuchs (2016) confirmed that it appears to be difficult for people struggling with weight problems to stay in a subject position, as their lived body is in a vulnerable and unbearable state. Therefore, it must be an important therapeutic goal to look behind the symptoms if possible, to make a shift of rigid objectification of one's own body towards a subject position (Gaete & Fuchs, 2016).…”
Section: To Be Objectified As a Human Beingmentioning
confidence: 94%
See 1 more Smart Citation
“…Health services focusing, for example, on lifestyle-changing programs might increase attempts to control the obese body, but this can also lead to an increased objectification of the body (Grønning et al, 2013). Gaete and Fuchs (2016) confirmed that it appears to be difficult for people struggling with weight problems to stay in a subject position, as their lived body is in a vulnerable and unbearable state. Therefore, it must be an important therapeutic goal to look behind the symptoms if possible, to make a shift of rigid objectification of one's own body towards a subject position (Gaete & Fuchs, 2016).…”
Section: To Be Objectified As a Human Beingmentioning
confidence: 94%
“…Further, he states that becoming oneself always begins through knowing and accepting oneself in the present (Batchelor, 2006;Kierkegaard, 1849). Gaete and Fuchs (2016) claimed that the public health service seems to enhance such objectification of the person's body. Health services focusing, for example, on lifestyle-changing programs might increase attempts to control the obese body, but this can also lead to an increased objectification of the body (Grønning et al, 2013).…”
Section: To Be Objectified As a Human Beingmentioning
confidence: 99%
“…Many works of this tradition have come to link anorexic psychopathology with complex alterity and "intercorporeity" processes [20][21][22][23][24][25][26][27][28]. According to a traditional proposition of phenomenology, we can distinguish two types of body experience.…”
Section: Anorexic Psychopathology and Body Experiencementioning
confidence: 99%
“…This first contribution is useful to our understanding of anorexic body experience because it demonstrates that it is possible to evoke body existence beyond the simple materiality of this body, or beyond its simple representation [21,28], and consequently beyond its state of slimness. An anorexic-lived body cannot be reduced to the marks of the disease.…”
Section: Anorexic Psychopathology and Body Experiencementioning
confidence: 99%
See 1 more Smart Citation